PROBLEMATICS OF DEVELOPING THE INDONESIAN CAPITAL CITY ON TRADITIONAL LAND: BETWEEN STATE INTERESTS AND PROTECTION OF INDIGENOUS COMMUNITIES - Nurrachman, Azzahra (Journal Social Sciences and Humanioran Review, 2024)
The relocation of Indonesia’s capital city to East Kalimantan is expected to serve as a solution to reduce regional disparities, promote equitable economic growth, and accelerate infrastructure development. However, in practice, there remains considerable uncertainty regarding the legitimacy and legal protection of the rights of Indigenous Peoples directly affected by the development of the new capital, Nusantara (IKN). The lack of meaningful involvement of Indigenous communities in the planning and decision-making processes poses a threat to the continuity of their culture, traditions, and living spaces—resources that have been sustainably managed across generations. This study aims to analyze the problems of developing the new capital city (IKN) on customary land. This study uses a normative juridical approach, emphasizing the study of relevant laws and legal documents. The results indicate that the development of the new capital city raises serious problems related to the survival of the Balik indigenous community. Indigenous communities are threatened with the loss of their customary territories, which they have traditionally controlled and utilized. Concerns about the loss of livelihoods, limited clean water, ecosystem damage, and the threat of criminalization continue to threaten indigenous communities. This situation reflects the denial of indigenous peoples' rights and reinforces their position as a marginalized group.